Hyvä jätkä ku Caligula – antiikin representaatioita suomenkielisessä rap-lyriikassa - Jokela, Maria (Pohjois-Suomen Historiallinen Yhdistys ry, 2025)
The influence of the Greco-Roman world is deeply embedded in all spheres of Western culture. Its stories, myths, and classical quotations are woven into everyday language and cultural expression, making their presence in popular poetic forms, such as rap lyrics, unsurprising. This article examines Finnish rap lyrics from the 2010s and 2020s that contain references to the classical world. Notably, references to Greek mythology are the most prevalent, with figures such as the Midas touch and the Trojan horse frequently used as idiomatic expressions. For example, these allusions serve as a means to critique contemporary societal issues and generational concerns, such as consumerism and biodiversity loss, as rap lyrics often reflect the socio-political context in which they are composed. Additionally, quotations from ancient authors are present in the lyrics, appearing in various forms—some as direct citations in Latin, others as modified versions, and some translated into Finnish. Overall, the use of references to the classical world in the analyzed lyrics is highly creative, revealing multiple layers of meaning upon closer examination. Moreover, the lyrics demonstrate that expressions rooted in classical antiquity seamlessly integrate into contemporary Finnish self-expression.